Impact of Radii Ratios on a Two-Dimensional Cloaking Structure and Corresponding Analysis for Practical Design at Optical Wavelengths - Nadia Anam; Ebad Zahir (International Journal of Optics)
This work is an extension to the evaluation and analysis of a two-dimensional cylindrical cloak in the Terahertz or visible range spectrum using Finite Difference Time-Domain (FDTD) method. It was concluded that it is possible to expand the frequency range of a cylindrical cloaking model by careful scaling of the inner and outer radius of the simulation geometry with respect to cell size and/or number of time steps in the simulation grid while maintaining appropriate stability conditions. Analysis in this study is based on a change in the radii ratio, that is, outer radius to inner radius, of the cloaking structure for an array of wavelengths in the visible spectrum. Corresponding outputs show inconsistency in the cloaking pattern with respect to frequency. The inconsistency is further increased as the radii ratio is decreased. The results also help to establish a linear relationship between the transmission coefficient and the real component of refractive index with respect to different radii ratios which may simplify the selection of the material for practical design purposes. Additional performance analysis is carried out such that the dimensions of the cloak are held constant at an average value and the frequency varied to determine how a cloaked object may be perceived by the human eye which considers different wavelengths to be superimposed on each other simultaneously.